Synthesis and Empirical Analysis of the Thermophysical Characteristics of GO-Ag Aqueous Hybrid Nanofluid Using Environmentally Friendly Reducing and Stabilizing Agents - M. Armstrong; M. Sivasubramanian; N. Selvapalam; R. Pavitra; P. Rajesh Kanna; Haiter Lenin (Advances in Materials Science and Engineering)
The remarkable potential of the carbon allotrope graphene and its derivatives in developing hybrid nanofluids has sparked considerable interest among researchers. These carbon nanoparticles offer excellent opportunities to blend with various metal or metal oxide nanoparticle binders to improve their material properties. This study focuses on investigating the synthesis, characterization, and thermophysical properties of silver- (Ag-) infused GO aqueous hybrid nanofluids with various weight percentages (0.025, 0.05, and 0.1 wt.%) using environmentally friendly reducing and stabilizing agents. Characterization of the hybrid nanofluids was performed using XRD, SEM, EDX, a UV-visible spectrometer, a particle size analyzer, and FTIR techniques. The thermal conductivity and viscosity of the GO-Ag hybrid nanofluids were experimentally determined in the temperature range of 293 K–333 K. Notably, the results indicated that the nanofluids with a concentration of 0.1 wt.% exhibited the most significant enhancement in thermal conductivity, with improvements of 15.22% at 293 K and 31.19% at 333 K compared to the base fluid. A mathematical model was developed based on the thermal conductivity experimental results using the response surface methodology (RSM). Overall, the results suggest that the silver nanoparticles-decorated aqueous graphene oxide hybrid nanofluid has promising potential as an innovative heat transfer fluid in various heat transfer applications.